Dynamic Planning for Product Platform and Module Based on Graph Theory - Wu, Yongming; Zhang, Han; Luo, Lifei; Xu, Yanxia (Manufacturing Technology Journal, 2017)
Aiming at the problem of platform planning and module identification in product family design, modular theory, implementation methods and objectives are studied in mass customization(MC), and a dynamic planning model is established for product platform and module. Firstly, the versatility and physical consolidation of existing variants are analyzed and expressed using directed and undirected graphs. And then a dynamic planning algorithm, in which the platform threshold and the module boundary parameters are set dynamically based on market demands, is proposed in product platform and module design. Secondly, potential parts are extracted for more variant products in product family design. Finally, the effectiveness of the proposed approach was demonstrated by the dynamic planning for parts of different humidifiers.
Keywords: Product platform; Modularization; Graph theory; Dynamic planning